Improving Reading Comprehension of The Tenth-Grade Students at Islamic Senior High School Through the Use of Sticky Notes Strategy - Septia Puspita Sari; Jamiluddin; Hasna; Budi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This review evaluates a study exploring the use of the Sticky Notes Strategy to enhance reading comprehension among tenth-grade students at Islamic Senior High School. The study adopts a quasi-experimental design involving 38 students, equally divided into experimental and control groups. Pre-tests and post-tests were administered, and data were analyzed using SPSS 23. The results indicate significant improvements in reading comprehension scores for the experimental group, with a mean difference of 27.789 (p < 0.05). Results showed that sticky notes significantly improved students' ability to identify main ideas by 30% compared to traditional methods. This strategy increased engagement and encouraged metacognitive interaction with texts. The findings underscore the potential of simple, interactive tools to foster deeper learning in EFL contexts and promote student-centered literacy practices in Indonesian classrooms.